2015
DOI: 10.1093/nar/gkv980
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of Dnmt2-dependent tRNA methylation by the micronutrient queuine

Abstract: Dnmt2 enzymes are cytosine-5 methyltransferases that methylate C38 of several tRNAs. We report here that the activities of two Dnmt2 homologs, Pmt1 from Schizosaccharomyces pombe and DnmA from Dictyostelium discoideum, are strongly stimulated by prior queuosine (Q) modification of the substrate tRNA. In vivo tRNA methylation levels were stimulated by growth of cells in queuine-containing medium; in vitro Pmt1 activity was enhanced on Q-containing RNA; and queuine-stimulated in vivo methylation was abrogated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 51 publications
1
94
0
Order By: Relevance
“…In cells grown in standard complete or minimal medium, tRNA Asp methylation as measured by RNA bisulfite sequencing was found to be rather low (approx. 14%–20% [10,12]). However, overexpression of the pmt1 + gene under an inducible promoter yields 100% tRNA Asp methylation, and tRNA Glu methylation is marginally increased, indicating that Dnmt2 levels in wild-type (wt) cells are limiting for in vivo tRNA methylation.…”
Section: Trna Methylation By the Dnmt2 Family Of Rna Methyltransfementioning
confidence: 99%
See 3 more Smart Citations
“…In cells grown in standard complete or minimal medium, tRNA Asp methylation as measured by RNA bisulfite sequencing was found to be rather low (approx. 14%–20% [10,12]). However, overexpression of the pmt1 + gene under an inducible promoter yields 100% tRNA Asp methylation, and tRNA Glu methylation is marginally increased, indicating that Dnmt2 levels in wild-type (wt) cells are limiting for in vivo tRNA methylation.…”
Section: Trna Methylation By the Dnmt2 Family Of Rna Methyltransfementioning
confidence: 99%
“…As kind of a “shot in the dark”, we therefore hypothesized that queuine might be the agent that, when introduced at G34 of tRNA Asp , stimulates Dnmt2-dependent tRNA methylation. Lo and behold, cultivating S. pombe in the presence of queuine resulted in an increase of in vivo tRNA Asp methylation to 100% [12]. This revealed an unanticipated link between queuine modification and Dnmt2-dependent C38 methylation (Figure 1).…”
Section: Trna Methylation By the Dnmt2 Family Of Rna Methyltransfementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it has also been shown that C38 tRNA methylation in Schizosaccharomyces pombe is regulated by queuine [87]. As 5mC at C38 has been shown to have a function in translational accuracy [84], these results suggest a novel and exciting mechanism that allows nutritional factors to modulate mRNA decoding and translation.…”
Section: Genome Recoding By Trna Modificationsmentioning
confidence: 99%